Endangered breeding sites of the Fire-bellied toad Bombina bombina in the Łomianki section of the Vistula River valley, central Poland - Prokopowicz, Adam; Romanowski, Jerzy (Studia Ecologiae et Bioethicae, 2016)
Field surveys for the Fire-bellied toad Bombina bombina were conducted in spring and summer 2013 and 2014. The study area is located in the Vistula River valley, north of Warsaw in Mazovia, central Poland. The area is of a high natural value and partially overlaps with two Natura 2000 areas: the Kampinos section of the Vistula River valley (PLH 140029) and the Middle Vistula River valley (PLB 140004). Two breeding sites of Fire- -bellied toads were detected in the vicinity of river dikes, including one in an ephemeral pond located in the flooded part of the river valley. The results document the decrease in number of breeding sites of the species. The surviving two local populations of Fire-bellied toads are endangered with illegal dumping of construction debris and the close vicinity of motocross track. To reduce the risk of extinction of local populations of Fire-bellied toads in Vistula valley, the authors discuss the proposition to enlarge existing Natura 2000 areas.